Evaluating Suppliers Using AHP in a Fuzzy Environment and Allocating Order Quantities to Each Supplier in a Supply Chain. (13th July 2022) - Lavanpriya, C.; Muthukumaran, V.; Manoj Kumar, P.
Abstract : The most challenging task in the supply chain is selecting the appropriate supplier, and it has a great influence on industry productivity growth. Because of the large budget allotted to raw materials, supplier selection is a critical issue for the industry's financial status. The right supplier in the industry drastically reduces problems throughout the supply chain. The several managers of a company were interviewed, and the most essential criteria considered by the managers when choosing their supplier firms were identified. In this study, Fuzzy-AHP and goal programming are combined to identify suitable suppliers and allocate orders in the supply chain. The mathematical models developed the goals of minimizing periodic budget, minimizing defect rate, maximizing the total value of purchase, and maximizing demand. To reach the desired values of periodic goals, the multiobjective multi-integer linear programming model is presented. A mathematical example is offered to show the effectiveness of suggested method. The Archimedean goal programming method is used to solve these multiple periods of single products within the Lingo 18.0 software package. Multiple period demand allocations to suppliers are calculated as X 11 = 9000, X 12 = 7800, X 13 = 7900, X 21 = 3434.9, X 22 = 5098, X 23 = 6002.56, X 31 = 100, X 32 = 100, and X 33 = 100. All the target values of budget, defective rate, and demand are achieved for all periods except the total values of purchasing. The results are subjected to sensitivity analysis. It will help a manufacturer for selecting a suitable supplier to allocate the order for maximizing the profit, improving the quality of product, enhancing the supplier buyer relationship, strengthening the supply chain, reducing the risk of purchasing decision, and improving customer satisfaction. Therefore, the supply chain is effective to supply the continuity of products.